PERSONAL FACTORS AS PREDICTORS OF INTENTION TO USE IT - Tutuk Ari Arsanti; Emalia Yuliasari (Jurnal Manajemen dan Kewirausahaan, 2018)
The relative power of personal factors such as innovativeness, perceived usefulness, ease of use, and attitude in predicting intention to use IT was tested with 35 students through a field experiment. A common employment website in Indonesia called jobstreet. com is used as a treatment channeling instrument as well as relevant audio and visual media. Simple and multiple regression were used to test the hypotheses. Our findings show that the personal factors such as personal innovation could predict perceived ease of use better than perceived usefulness. The other personal factors such as individual perception (perceived ease of use and perceived usefulness) could predict attitude for the next to effect intention to use IT